De Novo Designed Copper α‐Helical Peptides: From Design to Function. Issue 13 (31st March 2014) - Tegoni, Matteo
Abstract: De novo protein design is a fascinating and powerful approach to the design of metal sites in the interior of simplified protein scaffolds. A series of de novo designed copper peptides are herein described. They consist of peptide constructs that possess a secondary and tertiary structure, and that can be regarded as simplified proteins from which most of the structural complexity has been removed. Although relatively small, these copper peptides retain enough complexity to show features typical of proteins, such as enzyme‐like catalytic behavior or specific spectroscopic features. This review focuses on the de novo design of α‐helical constructs and in their use to devise different types of copper centers. Through the proper design of the peptide sequences, it has been possible to study the Cu‐triggered folding of peptide strands, which resulted in the isolation of enzyme regulators and biosensors for copper. Moreover, the use of Cys‐containing peptides allowed us to design sites structurally similar to the copper‐binding sites of biomolecules involved in copper trafficking and homeostasis. Finally, catalytic copper Type 2 sites capable of undergoing redox reactions and copper Type 1 and Type A centers with spectroscopic characteristics remarkably similar to those of natural proteins are discussed. Abstract : De novo designed α‐helical peptides have been used to design structural and functional copper sites in minimum protein scaffolds. The design of structural copper Type 1, Type 2, Type A, and Cu–SCys centers in α‐helical constructs is described. Catalytic copper Type 2 centers are also presented, along with their functional features.